1999
DOI: 10.1002/(sici)1520-6300(1999)11:4<531::aid-ajhb13>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling dynamic skinfold compression

Abstract: Real time compression of skinfolds was measured at three sites (triceps, abdominal medial calf), using a Slim Guide skinfold caliper adapted by the addition of a potentiometer, on eight males and eight females (age range 18–40 years). An average of eight trials for each subject at each site was used in modeling the compression curves. A mechanical model was developed, comprised of two parallel spring and viscous components in series with each other. $ Tt = Tinitial + F \left( { 1 \over k_1 } - \left\lceil { e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…In contrast to soft tissue, taut tissue is more resistant to pressure and is more difficult to form into a measurable skinfold. McRae [32] described a difference in tissue compressibility between men and women, while Ward et al [33] described a greater elasticity and lower viscosity of the skinfolds on females [33], most likely due to the different anatomy and biology of the fat tissue [34]. In the data on males, the skinfolds on the triceps, back, and thigh had the best scores in the BlandeAltman analysis.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to soft tissue, taut tissue is more resistant to pressure and is more difficult to form into a measurable skinfold. McRae [32] described a difference in tissue compressibility between men and women, while Ward et al [33] described a greater elasticity and lower viscosity of the skinfolds on females [33], most likely due to the different anatomy and biology of the fat tissue [34]. In the data on males, the skinfolds on the triceps, back, and thigh had the best scores in the BlandeAltman analysis.…”
Section: Discussionmentioning
confidence: 94%
“…With regard to the analysis of the evolution of the compressibility of the skinfolds as a function of sex, it was found that sex did not have an influence on the time at which the lowest value was found in the reading of the skinfold, with this being between 2.43 seconds and 2.90 seconds for the sample of men, and between 2.16 seconds and 3.00 seconds for the sample of women. Previous studies had hypothesized that the compressibility and stabilization of skinfolds might vary according to sex, given the influence of factors such as skin tension and thickness, distribution of connective tissue and blood vessels, and the distribution and characterization of fat mass [ 6 , 27 , 28 ]. However, thus far, there are no known studies that have analyzed this issue in real-life situations.…”
Section: Discussionmentioning
confidence: 99%
“…During the first two seconds of compression, the tissue fibres are reoriented in the initial phase (0⋅0 to 0⋅5 s) followed by stretching of the elastic components (0⋅5 to 2⋅0 s) and a brief exponential decrease in the thickness skinfold. At this point, the static compressibility plateau is reached ( 16 , 17 ) . Martin et al ( 19 ) identified a mean of 52⋅6 % static compressibility for 13 skinfold sites using a Harpenden® skinfold caliper in a sample of male and female human cadavers.…”
Section: Developmentmentioning
confidence: 98%
“…The physical, mechanical and functional specifications of the Harpenden®, Lange® and Slim Guide® skinfold calipers discussed in this report were reviewed and described based on original studies (4)(5)(6) and evidence from important complementary experiments (7,(14)(15)(16)(17)(18) . The digital illustrations presented below were made by the author of this report and are unique in their originality and richness of detail.…”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation